Global Activism and Humanitarian Disarmament
XVII, 272 p. 9 illus., 8 illus. in color.
Keywords: This book analyses the politics of the humanitarian disarmament community—a loose coalition of activist and advocacy groups, humanitarian agencies and diplomats—who have successfully achieved international treaties banning landmines, cluster munitions and nuclear weapons, as well as restricting the global arms trade. Two campaigns have won Nobel Peace Prizes. Disarmament has long been a dirty word in the international relations lexicon. But the success of the humanitarian disarmament agenda shows that people often choose to prohibit or limit certain violent technologies, for reasons of security, honour, ethics or humanitarianism. This edited volume showcases interdisciplinary research by scholars and practitioners seeking to understand the dynamics and impact of the new global activism on weapons. While some raise concerns that humanitarian disarmament may be piecemeal and depoliticizing, others see opportunities to breathe new life into moribund arms control policymaking. Foreword by 1997 Nobel Peace Prize Laureate Jody Williams. Matthew Breay Bolton is Associate Professor of Political Science and Director of the International Disarmament Institute at Pace University, USA. Sarah Njeri is Research Associate at King’s College London’s African Leadership Centre, UK. Taylor Benjamin-Britton has taught courses in international relations and international organization in the Department of Political Science at Temple University, as well as the Department of International Relations at Lehigh University, USA.